Fundamentals of Ecology - Odum, Eugene P; Barrett , Gary W (Australia : Cenage learning, 2005)
this book you will gain an integrated perspective on the field of ecology by exploring topics such as the ecological footprint, global climate change, soil and fire ecology, metapopulation dynamics and landscape sustainability. Using real world examples you will also learn how ecological principles can be applied to address issues such as resource management, conservation ecology etc.
Includes Gossary 511-534p.; References 535-582p.; Index 585-598p.
Keywords: Biology; Ecology; Environmental Biology